Implications of sulphur regulation on vessel use in Finnish seaborne trade - Tuomas Kiiski; Sini Laari; Tomi Solakivi; Juuso Töyli; Lauri Ojala (Denmark, 2022)
Purpose
Shipping is facing tightening regulations to mitigate its environmental footprint. For example, the policy to restrict ships’ fuel sulphur content to 0.1 % became effective in the Baltic Sea on 1.1.2015. The consequences of this policy – initially suggested to lead to modal shifts and substantial increase in costs – are still much debated. The objective of this paper is to find out how do ships calling Finnish ports in 2010-2017 have reacted on the implementation of the Sulphur Emission Control Area (SECA) by IMO in the Baltic Sea.
Design/methodology/approach
Annual list of all vessel port calls in Finnish ports together with vessel-by-vessel technical data obtained from Clarkson World Fleet Register comprise the research data. Descriptive statistical analysis is the main research method.
Findings
The results indicate that Roll on - Roll off  vessels are mostly affected by SECA regulation in terms of scrubber installations, while majority of ships calling at Finnish ports have switched to cleaner fuel grade. LNG appears to be an option involving only newbuildings.
Research limitations/implications
The implications of the SECA are analysed from the Finnish perspective. In the future, the analysis should be extended to other SECA countries to confirm the generalizability of the results.
Practical implications
The results provide insights to shippers and ship owners on how the transport flows in the Baltic Sea region have evolved in 2010-2017 in order to plan for future vessel investments.
Social implications
The results provide empirical evidence for policymakers on how the shipping market has adjusted on stricter sulphur regulations. These findings can be utilized when preparing for the global cap of 0.5% sulphur content in ships’ fuel, which will be effective by 2020.
Originality/value
The paper contributes to the discussion of economic impacts of environmental regulation in shipping by analysing how the implementation of the SECA has affected vessel distribution used in Finnish seaborne trade.
Keywords:     Shipping, Sulphur Emission Control Area, Baltic Sea, Finland
Proceedings of the 30th Annual NOFOMA Conference: Relevant Logistics and Supply Chain Management Research